Click-based thiol-ene photografting of COOH groups to SiO2 nanoparticles: Strategies comparison - Penelas, María Jazmín (2019)
We present the study of the anchoring of carboxylic groups on SiO2 nanoparticles from different approximations based on the photochemical radical thiol-ene addition (PRTEA) reaction: a photografting approach between mercaptosuccinic acid (MSA) and vinyl-modified SiO2 nanoparticles and the post-grafting on the surface of silica colloids of the silane precursor 2-((2-(trimethoxysilyl)ethyl)thio)succinic acid (TMSMSA), obtained from the PRTEA. These synthetic strategies were compared with a widely common derivatization methodology based on the nucleophilic attack of surface-anchored amino groups with succinic anhydride. The successful functionalization of the colloidal silica was confirmed by infrared spectroscopy (FTIR), zeta potential at different pH and contact angle measurements. We found that although these three approaches were valid for −COOH immobilization, they had a noticeable impact on the dispersability and agglomeration of the colloidal suspension at the end of the synthesis. Scanning electron microscopy, dynamic light scattering (DLS) and fluorescence correlation spectroscopy (FCS) measurements indicated that the PRTEA photografting between MSA and vinyl-modified SiO2 resulted in highly dispersed colloidal particles. On the other hand, the presence of surface −COOH groups was highly beneficial for redispersion of the colloidal material after lyophilization or freeze-drying procedures.